Development Of The Religious Tourism Attraction Of The Great Mosque Of Sultan Abdullah As A Leading Destination In Lebong Regency - Lavenia Aprilia Nia; Panji Suminar; Diyas Widiyarti (Dinasti Publisher, 2025)
This research aims to analyze the development of religious tourism potential at the Sultan Abdullah Grand Mosque as a leading destination in Lebong Regency. The study employs a descriptive qualitative approach with data collected through interviews, observations, and document studies. Informants were selected purposely, including the Head of Tourism, the Head of Social Welfare, mosque administrators, and tourists who had visited the Sultan Abdullah Grand Mosque. The data were analyzed using Miles and Huberman's techniques and Max Weber's Theory of Rational Action. The findings reveal that the Sultan Abdullah Grand Mosque has significant potential as a leading destination due to its historical value, unique architectural design, and adequate infrastructure. Efforts by various regional institutions, such as the Regional Government, Disparpora, and daily mosque administrators, have enhanced the appeal of this tourist site. However, challenges such as limited funding and park maintenance persist. The Lebong Regency Government has also undertaken various efforts to improve mosque facilities through infrastructure upgrades and extensive promotions. It is hoped that these strategies will attract more tourists, boost the local economy, preserve cultural and religious values, and establish the Sultan Abdullah Grand Mosque as a leading destination in Lebong Regency.